Men in my (historical) life (Historia, 2021)
Although more than forty years have passed since I graduated with a Bachelor of Arts degree from the University of Cape Town, I can still hear the icy tones of Professor H.M. Robertson, enrobed in his ancient academic gown long turned from black to a musty shade of green, as he addressed me : "Miss Swingler, would you and your noisy friends who are disrupting my class from the back row leave the room immediately". I cringe when I recall the episode, embarrassed by my lack of appreciation for Robertson's eminence and erudition as a leading international economic historian and economist. But then, in his book on the history of UCT, Howard Phillips has observed that Robertson, who had joined the staff in 1930 and was thus fairly old when he lectured to dissident students such as me, would deliver his carefully crafted lectures with "studied slowness".